Prevalence of Burnout Syndrome among volunteer psychologists providing psychological support in Italy during the COVID-19 pandemic: The role of workload - Pietro CRESCENZO; Livio TARCHI; Amelia RIZZO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: This study aims to explore the prevalence of Burnout Syndrome (BOS) among volunteer and non-volunteer psychologists and investigate the effects of volunteer hours and the number of weekly interventions on the dimensions of burnout: Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA). Methods: We analyzed a sample of individuals divided into groups of volunteer and non-volunteer psychologists. The prevalence of BOS and its dimensions were measured using the Maslach Burnout Inventory (MBI) and analyzed through MANOVA and linear regressions. A total of 468 psychologists (83.5% females; with an average age of 40.95 years ± 8.98) participated in the study, using a non-probabilistic convenience sample. Results: The overall prevalence of BOS was 17%, with volunteer psychologists (17.5%) and non-volunteer psychologists (16.2%). Significant results were found for the number of weekly volunteer hours and the number of weekly interventions, which were predictors of increased levels of EE and DP (p<.005; p<.02 for EE and p<.005; p<.01 for DP). For Personal Accomplishment, only volunteer hours had a significant negative impact (p<.01). Conclusions: The findings suggest that the workload of volunteer activities can significantly contribute to increased emotional exhaustion and depersonalization. Organizations are recommended to moderate the workload of volunteers and implement adequate support to mitigate the risk of burnout. Further research is needed to deepen these findings and develop effective interventions.